Securities fraud detection, prevention, and control - Straney, Louis L., 1946- (New York : Wiley, 2011)
"The first complete, expert guide to securities and investment fraud Filled with expert guidance for detection and prevention of all kinds of securities fraud and investment misconduct, Securities Fraud helps you identify red flags of fraud and offers practical ways to detect and prevent it. Written by a Wall Street professional with three decades of experience spanning the most critical period of our financial markets This book challenges classic fraud theories, describing how to dismantle information silos that permit fraudsters to conceal their activities. Begins with an overview of the evolution of securities regulation and the impact of securities fraud. Offers real cases and examples which illustrate recurring themes and red flags. Provides the first guide of its kind to offer a complete look at the various kinds of securities fraud and investment misconduct Securities Fraud is the essential guide you need for a bird's-eye view of fraud that may be taking place even now within your own organization and with your portfolio."--
Includes index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Securities fraud; Electronic books